Knowledge Analysis of PGSD FKIP University of Mataram Students on Physical Education, Sports, and Health Concept - Prayogi Dwina Angga; Umar Umar (Departement of Mathematics Education, 2023)
As a very unique subject, Physical Education, Sports, and Health (PJOK) is here to be a bridge that combines the three learning domains namely cognitive, affective and psychomotor. This study aims to analyze the knowledge of students of the Elementary School Teacher Education Study Program (PGSD), Faculty of Teacher Training and Education, University of Mataram on the concepts of physical education, sports, and health which are presented in the curriculum courses. The questions that appeared in the questionnaire were developed based on the concepts of physical education, sports, and health as subjects which were divided into three main variables, namely (1) the definition of PJOK; (2) the purpose of the PJOK; (3) PJOK activities. The collected data were analyzed using the Guttman scale by giving a score of 1 for the correct answer and 0 for the wrong answer. PGSD students have a very good level of knowledge of the PJOK concept with a percentage of 84.09%. In terms of the main variable PJOK, student knowledge is in a good category (92.44%). For the PJOK objective variable, a percentage of 82.05% is also included in the very good category. Meanwhile, the PJOK activity variable obtained a percentage result of 78.30% in the good category. Searching for students' knowledge of the PJOK concept is one of the efforts to improve the quality of PJOK learning in order to optimize the achievement of learning objectives amidst limitations and various obstacles.